AMPK as a Bioenergetic Checkpoint in Neurons: Conditional Permission for Synaptic Plasticity - Pollo, Gracia Alice Victoria (JURNAL BIOS LOGOS, 2025)
Synaptic signaling and plasticity require a lot of energy. Those two pathways occurance differ based on energy availability. Synaptic signaling can occur rapidly but plasticity depends on sustained energy availability. This makes neurons need to assess whether sufficient energy is present to support plasticity. Adenosine monophosphate–activated protein kinase (AMPK) is a central cellular energy sensor, yet its role in determining the energetic permissibility of synaptic plasticity has not been clearly defined. This review proposes a conceptual framework in which AMPK functions as a bioenergetic checkpoint for synaptic plasticity. Evidence indicates that AMPK activity is tightly coupled to cellular energy status. Under high-energy conditions, low AMP and high ATP levels limit AMP binding to the γ subunit. This makes the β subunit remains non-myristoylated and the α subunit unphosphorylated thus maintaining AMPK in an inactive state. This results in permitted synaptic plasticity. During low energy condition, elevated AMP and reduced ATP promote AMP binding to the γ subunit. The binding then induce myristoylationn of β-subunit and phosphorylation of the α subunit at threonine 172 (Thr172). This cascade activate AMPK. Activated AMPK suppresses energy-consuming processes, thereby restricting synaptic plasticity. Through these mechanisms, AMPK converts fluctuations in cellular energy into a threshold-based decision that determines whether synaptic activity is permitted toward long-term plasticity in preserving bioenergetic homeostasis. This framework positions AMPK as a central bioenergetic checkpoint linking cellular energy status to the permission of synaptic plasticity.